2023
DOI: 10.1002/fft2.299
|View full text |Cite
|
Sign up to set email alerts
|

Tomato and human health: A perspective from post‐harvest processing, nutrient bio‐accessibility, and pharmacological interaction

Abstract: Solanum lycopersicum, which is commonly known as tomato, not only serves as a dietary fruit vegetable but also a functional food that protects humans against chronic degenerative illnesses such as diabetes microvascular complications, viral diseases, and cancers. The nutritional benefit of tomato is largely attributed to its phytonutrient composition. The influence of post‐harvest processing methods, digestion process, and compounds interaction on the bio‐accessibility of phytonutrients are key aspects to cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Figure 1 reveals a significant increase in total soluble sugar (TSS) and total acidity (TAC) accumulation in tomato fruits growing under DS conditions; however, protein content was reduced under the same conditions, in comparison with WW watered plants. Furthermore, AMF, C1, C2, AMF+C1, and AMF+C2 plants increased TSS accumulation (24,13,22,49, and 42%, respectively), TAC (6,11,16,9, and 15%, respectively) and protein content (49,69,81,87, and 65%, respectively), compared with control plants tested under DS conditions. In WW conditions, TSS and protein content increased substantially with the application of biostimulants, with a particularly marked increase recorded with AMF+C1 for TSS contents, and C1 for protein.…”
Section: Osmotic Solutes Changesmentioning
confidence: 83%
See 2 more Smart Citations
“…Figure 1 reveals a significant increase in total soluble sugar (TSS) and total acidity (TAC) accumulation in tomato fruits growing under DS conditions; however, protein content was reduced under the same conditions, in comparison with WW watered plants. Furthermore, AMF, C1, C2, AMF+C1, and AMF+C2 plants increased TSS accumulation (24,13,22,49, and 42%, respectively), TAC (6,11,16,9, and 15%, respectively) and protein content (49,69,81,87, and 65%, respectively), compared with control plants tested under DS conditions. In WW conditions, TSS and protein content increased substantially with the application of biostimulants, with a particularly marked increase recorded with AMF+C1 for TSS contents, and C1 for protein.…”
Section: Osmotic Solutes Changesmentioning
confidence: 83%
“…For instance, Morocco produces the equivalent of 3 million tons of tomatoes, most of which are destined for fresh consumption [ 11 ]. Moreover, tomato fruit plays an important role in protecting human health, thanks to its richness in minerals, vitamins, essential amino acids, lycopene, ascorbic acid, antioxidants, and dietary fiber [ 10 , 12 , 13 ]. These compounds are essential in reducing oxidative stress and inflammation, which supports the immune system and helps to protect against chronic diseases such as diabetes and various cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-enzymatic antioxidants of plants, such as vitamins, glutathione, carotenoids, flavonoids, and resveratrol help reduce oxidative stress-related damage by efficiently utilizing different high-capacity reductases that enable them to effectively regulate the cellular redox status [ 2 , 3 ], which guarantees the nutritional value of plant foods. Research has demonstrated that the antioxidant activity of phytonutrients, such as ascorbic acid and carotenoids is reduced by nearly 50% after being subjected to intestinal digestion, with a significant decrease in the average concentration of bioactive compounds [ 4 ]. Furthermore, a minimum daily intake of 400–500 g of fruits and vegetables has been recommended by the World Health Organization for the prevention of hypertension, stroke, and cardiovascular disease and amelioration of renal disease and other micronutrient-related deficiencies [ 5–7 ].…”
Section: Introductionmentioning
confidence: 99%